Dampak Penambangan Pasir Terhadap Kondisi Sosial Ekonomi Masyarakat Di Desa Batu Sondat Kecamatan Batahan Kabupaten Mandailing Natal Provinsi Sumatera Utara - Hayatun Nupus; Alexander Syam; Nisye Frisca Andini; Serly Muchlian (Kilau Publishing, 2024)
This research aims to obtain information and data descriptions about the impact of sand mining on the socio-economic conditions of the community in Batu Sondat Village, Batahan District, Mandailing Natal Regency. The type of research used is qualitative with descriptive methods. The informants in this study amounted to 21 people, namely the Deputy Head of Batu Sondat Village, Sand Mine Owners, Sand Mine Workers, Sand Buyers, and the Community. The types of data required are Primary and Secondary data types taken with the Snowball Sampling technique. Data collected by Observation, Interview, and Documentation techniques. The data analysis used is the Data Reduction Stage, the Data Presentation Stage, and the Conclusion Drawing Stage. The results of the study found that: The Impact of Sand Mining on the Socio-Economic Conditions of the Community is: Where the sand mine was established in Batu Sondat Village, it has received permission from the Village Head and all Customary Members in the Village and is well accepted by the community and there are also people who are less accepting of the establishment of this sand mine on the grounds of making river water polluted. However, after the establishment of this sand mine, the community's economy increased. Unemployment in Batu Sondat Village has decreased, many people get jobs from this sand mine so that people can meet their daily needs.